Synthesis of Metal–Curcumin Complex Compounds (M = Na⁺, Mg²⁺, Cu²⁺) - Peni Peni; Risya Sasri; Imelda Hotmarisi Silalahi (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2020)
Curcumin complex compound, MLn (L = curcumin; M = Na+, Mg2+, Cu2+) has been synthesized from the reaction between curcumin and metal precursors (NaCl, MgSO4.7H2O, CuCl2.2H2O) in ethanol under reflux conditions. Synthesis takes place through the reaction between the metal ions Na+, Mg2+, or Cu2+ as the central atom and curcumin as the ligand. Curcumin has been consumed after the reaction lasts for four hours, shown by thin-layer chromatography in which a new spot appears at higher Rf as the spot of curcumin disappears in the reaction mixture. Compared with the spectrum of curcumin, the FTIR spectra of the complexes show changes in the absorption bands and shifts of wave numbers particularly in absorption bands of phenolic –OH and C=O enol groups which strongly indicates the coordination of metal ions with the curcumin ligand which is proposed to be in β–1,3 diketone system. Also, the FTIR spectra of the reaction product showed typical absorption bands for the metal-oxygen group, M–O, at 524 cm–1, 670 cm–1 and 470 cm–1 in Na+–curcumin, Mg2+–curcumin and Cu2+–curcumin, respectively.